Pengaruh Domino Effect Terhadap Hasil Penjualan Produk - Radiastari, Mirza; Raditantri, Risti; Din, Winda Widya i; Sanjaya, Rendi David (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the domino effect of product promotion on the sales of other products within companies that have a multi-product portfolio. Data were collected from 50 companies, focusing on two main products during the promotion period. The results show that the promotion of product A significantly affected the sales of product B, with an average increase of 15%. Multiple linear regression analysis indicated a coefficient of 0.45 (p < 0.05), signifying a significant positive impact of product A promotion on product B sales. However, some companies reported a decrease in other product sales due to the dominant focus on the promoted product. Factors such as product category similarity, bundling strategy, and brand loyalty were key drivers of the domino effect. This study also highlights the importance of coordinated promotion across the product portfolio and efficient stock management. Therefore, this research provides strategic implications for marketing managers to optimize cross-product sales within the portfolio through more integrated promotional strategies.